The Philiki Etaireia Revisited: In Search of Contexts, National and International - Yakovaki, Nassia (The Historical Review/La Revue Historique, 2014)
It is perhaps not an exaggeration to say that studies on the Philiki Etaireia (1814-1821), a field of historical research that has evolved in a rather marginal, if not erratic way, are lately at a standstill; at the same time, however, the Age of Revolution – and, more to the point, the until recently understudied post-Napoleonic decades – is the object of a remarkable renewal of interest among historians internationally. This essay tries to place the life and deeds of the Philiki Etaireia once more on the agenda of social and political history of the period, not only of the Balkans and the Ottoman Empire, but also of post-Napoleonic Europe, by revisiting the case of this (much acclaimed in the Greek national narrative) secret society and bringing forward possible new contexts for better understanding its emergence and development.